2019
DOI: 10.7716/aem.v8i2.983
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Polarization-Independent Dual-Band Electromagnetically Induced Transparency-Like Metamaterial

Abstract: In this study, the classical analog of single and dual-band electromagnetically induced transparency is demonstrated with a four-fold symmetric metamaterial consisting of a Minkowski fractal ring resonator surrounded by a square ring resonator. The proposed metamaterials show high transmission ratios at the polarization independent resonances, as confirmed by the applied two different numerical methods. Delay-bandwidth products are found to be 0.34 and 0.61 at the resonances of the dual-band metamaterial. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In order to make practical devices applicable for ultrasensitive sensing and slow light effect, it is very crucial to design the double-band EIT MMs that have polarization independent response. Although polarization independent double-band EIT MM has been reported very recently in the gigahertz frequency regime [48], none of the studies on double-band EIT phenomenon in terahertz metamaterials have reported a polarization independent effect to the best of our knowledge. We have addressed this important aspect in this paper.…”
Section: Introductionmentioning
confidence: 89%
“…In order to make practical devices applicable for ultrasensitive sensing and slow light effect, it is very crucial to design the double-band EIT MMs that have polarization independent response. Although polarization independent double-band EIT MM has been reported very recently in the gigahertz frequency regime [48], none of the studies on double-band EIT phenomenon in terahertz metamaterials have reported a polarization independent effect to the best of our knowledge. We have addressed this important aspect in this paper.…”
Section: Introductionmentioning
confidence: 89%
“…14,15 The main advantage of metamaterials is that they are able to provide properties that are not possessed by conventional materials based on structural changes. 16 However, this can also be a disadvantage. This is because once a final structure is developed, results can no longer be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…A single and dual-band EIT effect was investigated in a microwave metamaterial, which exhibited high transmission. 16 A polarization insensitive double-band EIT phenomenon is studied experimentally in the terahertz band. 10 These results can be applied in the fields on filters and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi dark modes can couple with the incident electric field, however as compared to the bright mode it has weaker confinement. Several MM configurations have been exploited to exhibit multi-band EIT effect in the microwave 34,35 , infrared 36 as well as in the terahertz frequency regimes 3739 . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%